Moisture migration in a grain column subjected to drying - Hawlader, Mohammad Nurul Alam; J. Chowdhury, Md. Shafique (IIUM Press, 2011)
In this paper. a mathematical model has been developed to predict temperature and moisture distribution within a column dryer taking into account the influence of the change of air moisture on the grain moisture through the sorption isotherm. In the development of the energy equation, the influence of moisture contents on the properties of the material has been considered. The resulting unsteady, nonlinear, coupled differential equations are solved numerically, using orthogonal collocation method. A detail parametric study has been performed to identify important variables. The model is also applied to predict moisture migration under conditions approximating both low and high temperature in-storage drying of grains. The predicted results show good agreement with the experimental values.